A companion to Ancient near Eastern art - Gunter, Ann Clyburn 1951- (Newark John Wiley & Sons, Incorporated, 2018)
Intro -- Table of Contents -- Preface -- CHAPTER ONE: The "Art" of the "Ancient Near East" -- Introduction -- Defining the "Ancient Near East" -- Periodization and Chronology of the "Ancient" Near East -- Modern Frameworks for an "Ancient Near Eastern Art" -- Did the Ancient Near East in Fact Produce "Art"? -- Comparative Approaches -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- PART I: APPROACHES AND METHODS OF ANALYSIS AND INTERPRETATION -- CHAPTER TWO: Art and Material Culture -- Introduction -- The Mechanical Reproduction of Images -- Art, Material Culture, and Social Scale -- The "Bureaucratic Eye" -- Image, Commerce, and Cosmology -- Cult Images and the Mixture of Materials -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER THREE: Meaning and Interpretation -- Introduction -- New Perspectives from Anthropology and History -- The Methods of Art History and the Ancient Near East -- Text and Image -- The "Fribourg School": The Bible and Ancient Near Eastern Iconography -- The Purpose and Persistence of Images -- Missing "Images" and Their Interpretation -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER FOUR: Style -- Introduction -- Challenges of Style for the Study of Ancient Near Eastern Art -- Potentials of Stylistic Analysis, I: Selected Examples from Ancient Near Eastern Art -- Potentials of Stylistic Analysis, II: Ancient Near Eastern Glyptic -- Seal Styles and the Achaemenid Empire (ca. 550-330 BCE) -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER FIVE: Connoisseurship and Classification -- Introduction: Issues of Terminology -- Connoisseurship and Classification -- Connoisseurship, Classification, and Style: Passive Reflection of Normative Rules to Means of Active Communication and Information Exchange
Cases of Connoisseurship and Classification in Near Eastern Art History -- Ivories of the Early First Millennium BCE -- A View from Abroad -- Glyptic -- Neo‐Assyrian Reliefs -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER SIX: Visual Culture -- Introduction -- Hierarchies of Objects: Defining "Art" -- Disembodied Images: Reconstructions and Simulacra -- The Image in/on the Stone -- Images as Constructions of/by Culture -- Space at Babylon -- Visuality -- The Materiality of Gold -- Conclusion: Why (Not) Visual Culture Studies? -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER SEVEN: Technical Examination and Material Analysis -- Introduction -- Dating -- Analytical Tools -- Visual Analysis -- Structural Analysis -- Elemental Analysis -- Material Identification and Manufacture -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER EIGHT: Gender and Sexuality -- Introduction -- Making and Breaking the Mother Goddess Paradigm -- The Emerging Male in Mesopotamian Narrative Art -- Nudity and Sex: Titillation, Fertility, Protection -- Gender Ambiguity and Intersexuality -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER NINE: Semiotics, Reception Theory, and Poststructuralism -- Introduction -- Nonverbal Communication and How It Functions -- Semiotics: The World of Signs -- Reception Theory: The Receiver's Role in Nonverbal Communication -- Poststructuralism -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- PART II: CRITICAL TERMS AND CONCEPTS -- CHAPTER TEN: Representation -- Introduction -- An Expanded Definition of Representation -- Art History and Approaches to Interpreting Representations -- The Material Perspective: The Ontology of Mesopotamian Objects -- Neo‐Assyrian Art and the Vocabulary of Representation -- Beyond Assyria: The Luwian and Aramaean Kingdoms -- Conclusions
GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER ELEVEN: Narrative -- Introduction -- Narrative in the Art of Mesopotamia -- Obligation and Action -- Legal Transactions and Ritual Narratives -- The Birth of Historical Narratives -- The Cycle of Past and Future -- Assyrian Warfare and Ritual -- Conclusion: The Beginning and End of Mesopotamian Narrative -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER TWELVE: Ideology -- Introduction: Religion and Ideology -- Tradition and Ideology -- The Early Materialization of Tropes Pertaining to Royal Ideology -- Ritual -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER THIRTEEN: Ritual -- Introduction -- Disciplining Ritual: Contributions from Anthropology -- Between Art History and Archaeology: Enclosing and Disclosing Ritual -- The Hidden and the Everyday at Çatalhöyük -- Neo‐Assyrian Apotropaic Figurine Deposits -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER FOURTEEN: Agency -- Introduction -- Object Agency in Mesopotamia -- Etic and Emic Descriptions -- Agency Theory -- Alfred Gell's Art and Agency -- Approaches to Art -- Object Agency -- Object Agency and the Ancient Near East -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER FIFTEEN: Aesthetics -- Introduction -- Aesthetics and Perception, Senses and Communication -- Principles of Aesthetic Judgment -- Value and Prestige -- Aesthetic Modalities -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- PART III: MATERIALS, MEDIA, AND ARTISTIC ENVIRONMENTS -- CHAPTER SIXTEEN: Statuary and Reliefs -- Introduction: Terminology and Approaches -- The Objects: Type, Size, Material, Context, Findspot, Date, and Origin -- Who/What is Depicted: Figures' Identity, Portraiture, Narratives -- Who Made Sculpture for Whom: Artists, Patrons, Audiences -- Sculptures' Lives: Consecration, Maintenance, Maltreatment
Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER SEVENTEEN: Glyptic -- Introduction -- Material, Form, and Size -- Sealings: How Seals Were Used -- Purpose and Importance of Seals in Antiquity and Today -- Seals as the Mass Media of Antiquity -- Private Seals vs. Institutional or Group Seals -- The Iconography of Seals: Between Narrative Medium and Symbolic Representation -- The Main Themes and Motives on Seals: Seventh to First Millennium BCE -- Individual Themes and Motives -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER EIGHTEEN: Religious Architecture -- Introduction -- The Eanna Precinct at Uruk: Late Uruk Period -- Temple Building in Early Dynastic Mesopotamia: Khafajah -- Innovations in Temple Planning at the End of the Third Millennium BCE -- Regional Distinctions in the Early Second Millennium BCE -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER NINETEEN: Palaces and Elite Houses -- Introduction -- The Development of Palaces in Greater Mesopotamia and Syria (ca. 3000-2000 BCE) -- Mesopotamia and Syria in the Second Millennium BCE: Kingdom to Empire -- Neo‐Assyrian and Neo‐Babylonian Palaces: First Millennium BCE -- Palaces in Hittite Anatolia (ca. 1650-1180 BCE) -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER TWENTY: Rock Reliefs and Landscape Monuments -- Introduction -- Inscribing and Reinscribing Place -- Rock‐Carving as Colonization of Landscapes and Places -- Apparitions on the Living Rock -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER TWENTY-ONE: Reconstructing Artistic Environments -- Introduction -- Artistic Environments of the Prehistoric Near East -- Artistic Environments of the Early State -- The Territorial State -- The Imperial State -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES
PART IV: INTERACTIONS WITH NEIGHBORING REGIONS AND ARTISTIC TRADITIONS -- CHAPTER TWENTY-TWO: The Ancient Near East and Egypt -- Introduction -- Image Exchange in the Fourth Millennium: Service to Technology and State Formation -- Artistic Exchange in the Third and Second Millennia: Ideology Exported, Technique and Form Imported -- The Late Bronze Age and the Egyptian New Kingdom -- The International Context of the Late Bronze Age -- Interconnections in the First Millennium BCE -- The Statue of Darius and Egypt in the Achaemenid Era (ca. 525-330 BCE) -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER TWENTY-THREE: The Ancient Near East and the Bronze Age Aegean -- Introduction -- The Early Bronze Age (ca. 3000-2000 BCE) -- The Middle Bronze Age (ca. 2000-1600 BCE) -- The Late Bronze Age (ca. 1600-1200/1100 BCE) -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER TWENTY-FOUR: Near Eastern Art in the Iron Age Mediterranean -- Introduction -- Early Networks and the Cypriot Connection -- Orientalia: Ivories, Bowls, and Cauldrons -- Oriental and Orientalizing Art in Crete: 900-600 BCE -- Oriental Art in Early Iron Age of Greece: The Cemeteries of Athens and Lefkandi (Euboia) -- A New Context: The Great Sanctuaries of Olympia and Samos (Heraion) -- Near Eastern Art in Latium and South Etruria -- Summary and Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- PART V: INTERSECTIONS WITH ARCHAEOLOGY, COLLECTING, AND CULTURAL HERITAGE -- CHAPTER TWENTY-FIVE: Archaeology and the Art of the Ancient Near East -- Introduction -- Stratigraphy and Provenance -- The Afterlife of Monuments -- Functional Contexts -- Analytical Methods -- The Significance of New Discoveries -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER TWENTY-SIX: Cultural Heritage across the Middle East, Ancient and Modern -- Introduction
"Cultural Heritage" and its Uses in the Ancient Near East
Keywords: Art, Middle Eastern; Art, Ancient-Middle East; Art, Ancient ; Middle East; Electronic books; Aufsatzsammlung